Variability and Performance Evaluation of Released Linseed Varieties for Yield and Related Traits in South Gondar Zone, Ethiopia. (18th November 2022) - Amare, Kassahun; Abebe, Getaneh
Abstract : Even though numerous improved linseed varieties have been released in Ethiopia, the mean seed yield per unit area of the crop remains low due to poor access to improved varieties. To improve the crop's production and productivity, testing the performance of improved linseed varieties in potential agroecologies where the varieties have never been grown before is an essential activity. Additionally, understanding the amount of genetic variation that is available within the linseed germplasm using genetic traits is also critical to the successful and sustainable improvement program of linseed. The main objective of this research was to evaluate the performance of improved linseed varieties and their genetic variability for seed yield and related traits in the Lay Gayint district, South Gondar zone, Ethiopia. The experiment was conducted following a randomized complete block design with three replications, and nine released varieties and one local linseed variety were assessed in the study. Seed yield and yield-related traits were collected and subjected to a combined analysis of variance. The result shows that there was a significant difference between the tested linseed varieties for all examined traits, indicating the existence of genotypic variation between the experimental linseed varieties. The varieties Berene, CI-1525, Yadeno, and Furtu produced relatively higher seed yields, with an average of 894.28, 879.36, 823.28, and 820.85 kg·ha −1, respectively. Approximately 70% of the evaluated varieties produced higher seed yields than the local variety. The analysis of variance also resulted in a significant variety by year interaction effect for height of the plant, number of tillers, capsule number/plant, and seed yield, indicating the inconsistency of the varieties across the two growing seasons. Higher genotypic coefficient of variation (GCV) and phenotypic coefficients of variation (PCV) (>20%) coupled with high heritability estimated values (>80%) were observed for seed yield per hectare, the number of capsules per plant, and tiller number. Seed yield and the number of capsules per plant provided higher genetic advance estimations. To make the selection more successful, breeders should concentrate on traits with high genotypic variance and heritability estimates, and promising varieties should be introduced and dispersed within the research area.